A comparison of flipped learning with gamification, traditional learning, and online independent study: the effects on students' mathematics achievement and cognitive engagement. Issue 4 (18th May 2020) - Lo, Chung Kwan; Hew, Khe Foon
ABSTRACT: This study examines Grade 9 students' mathematics achievement and cognitive engagement under three different instructional approaches: traditional learning, flipped learning with gamification, and online independent study with gamification. The duration of the study lasted an entire school year. The central theories underpinning flipped learning with gamification design were based on the first principles of Instruction and self-determination theory. A mixed methods approach was used with quantitative (i.e., tests and an optional assignment) and qualitative (i.e., student interviews) methods applied. The test results indicate that students in the flipped class ( n  =  28) significantly outperformed those in the traditional ( n  =  27) and online independent study ( n  =  21) classes. In addition, flipped learning with gamification promoted students' cognitive engagement better than the other two approaches. The findings of student interviews suggest that peer interactions inside the flipped classroom were critical to promoting students' mathematics achievement and cognitive engagement, as opposed to online learning resources and gamification per se. In future practice, teachers can ground their flipped classroom design in the theoretical framework proposed in this study.